2023
DOI: 10.20961/carakatani.v38i2.69384
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod Community Structure Indicating Soil Quality Recovery in the Organic Agroecosystem of Mount Ciremai National Park’s Buffer Zone

Isma Dwi Kurniawan,
Ida Kinasih,
Rahmat Taufiq Mustahiq Akbar
et al.

Abstract: <a name="_Hlk128052096"></a><a name="_Hlk128036424"></a><span lang="EN-US">The</span><span lang="EN-US"> Mount Ciremai National Park (TNGC) buffer zone is designed to support conservation efforts. However, agriculture in this area is dominated by conventional farming that excessively uses synthetic fertilizers, which threatens soil quality. Introducing an organic fertilizer and plant growth-promoting rhizobacteria (PGPR) is expected to enhance soil quality recovery in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…These taxa are important in the digestion of organic matter, and as a result, they play a key role in nutrient cycling. Additionally, in a recent study by Kurniawan et al [59], when comparing conventional and agroforest systems, they found that Zygentoma were entirely absent in conventional croplands, indicating a sensitivity to agrochemicals. It is unsurprising to see significantly higher Hemiptera richness with increasing crop richness, as Hemiptera are significant crop pests.…”
Section: The Effect Of Cropland Managementmentioning
confidence: 94%
“…These taxa are important in the digestion of organic matter, and as a result, they play a key role in nutrient cycling. Additionally, in a recent study by Kurniawan et al [59], when comparing conventional and agroforest systems, they found that Zygentoma were entirely absent in conventional croplands, indicating a sensitivity to agrochemicals. It is unsurprising to see significantly higher Hemiptera richness with increasing crop richness, as Hemiptera are significant crop pests.…”
Section: The Effect Of Cropland Managementmentioning
confidence: 94%
“…In addition to these factors, the period of implementation of organic management at the research site, which has only been implemented for approximately 2 years, since 2020, also has the potential to have an impact on the research results obtained. According to Chabert and Sarthou (2020) and Kurniawan et al (2023) on agricultural land, changes to the management system take several years to create an ecological balance and provide services to the land ecosystem.…”
Section: The Distribution Of Earthworms Population Density Under Diff...mentioning
confidence: 99%
“…Organic matter affects soil and plant biomass. Additionally, organic farming uses ecofriendly insecticides (Kurniawan et al, 2023). Organic farming improves soil quality, land sustainability, and crop quality.…”
Section: Introductionmentioning
confidence: 99%